Relation of Type 2 Myocardial Infarction and Readmission With Type 1 Myocardial Infarction in Hypertensive Crises (from a Nationwide Analysis) - (:unkn) unknown (EXCERPTA MEDICA INC-ELSEVIER SCIENCE INC, 2021)
Type 2 myocardial infarction (T2MI) is an ischemic injury that occurs due to a mismatch between myocardial oxygen supply and demand. T2MI can occur with hypertensive crisis. Nevertheless, the impact of T2MI on hypertensive crisis outcome is poorly understood due to limited data. This study was a retrospective analysis of the National Readmission Database year 2018. Patients were included if the primary diagnosis was hypertensive crisis, hypertensive urgency, or hypertensive emergency. Patients were excluded if they had type 1 myocardial infarction (T1MI), severe sepsis, septic shock, gastrointestinal bleeding, or hemorrhagic anemia at index admission. The primary outcome was 90-day readmission with T1MI. Secondary outcomes were in-hospital mortality, length of stay, resource utilization, and all-cause 90-day readmission. Subgroup analysis was done according to urgency and emergency presentation. A total of 101,211 index hospitalizations were included in our cohort, of whom 3,644 (3.6%) received a diagnosis of T2MI. A total of 912 patients were readmitted within 90 days with T1MI. T2MI was an independent predictor of 90-day readmission with T1MI (adjusted odds ratio [aOR] 2.64, 95% confidence interval [CI] 1.90 to 3.66, p <0.01). Subgroup analysis including only hypertensive urgency and hypertensive emergency yielded similar results (aOR 2.80, 95% CI 1.56 to 5.01, p <0.01 and aOR 2.28, 95% CI 1.59 to 3.27, p <0.01, respectively). In conclusion, T2MI was an independent predictor of poor outcome in patients presenting with hypertensive crisis. Further studies are needed to guide the management of T2MI in this population. (c) 2021 Elsevier Inc. All rights reserved. (Am J Cardiol 2021;161:56-62)
Keywords: BLOOD-PRESSURE; ASSOCIATION; MORTALITY; OUTCOMES